(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
Wilman Ordoñez Iturralde’s book, "La rockola en Guayaquil. Ensayo sobre la música y la cultura popular del despecho", is a significant contribution to studies on popular music in Guayaquil. Its author, a researcher and folklorist with a long trajectory, brings the reader closer to the historical narration from everyday life; a story that is permeated with autobiographical elements, but full of ethnographic interventions: interviews, field visits to bars and lupanars, exercise of memory and identity. The reason for its publication, among many things, was the systematic disappearance, not only of the jukebox, but also of the music, places and people that were part of the author’s life. The presence/absence of the rockola, has served the researcher to organize, as a prelude, a study on the different elements of popular music in Guayaquil: music stores, periodicals, the creation and self-affirmation of the coastal identity, the presence of phonograms produced by the record labels Odeon, Panart, RCA Victor, the cabarets and brothels circuit, local and international characters that were linked to popular music in the city. Because the distinctive feature of the book is the impact that popular music has had on the city.